A Tale of Africa Today : Balancing the Lives and Livelihoods of Informal Workers During the COVID-19 Pandemic - Nguimkeu, Pierre (Washington, DC: World Bank, 2020)
In Sub-Saharan Africa (SSA), more than 80 percent of workers find their livelihoods in the informal sector. They are artisans and shop owners, fishers and divers, tailors and weavers, truck drivers and market sellers, among many other informal jobs. In the era of the COVID-19 (coronavirus) pandemic, saving lives and protecting livelihoods are both deeply challenging in SSA countries with high informality and almost no social protection. Informal workers and their families are most vulnerable to the disease, as they toil in crowded bazaars and busy streets. Moreover, informal workers are typically poor and cannot stockpile food or cash for a long lockdown. Strict containment measures directly jeopardize their income, their livelihoods, and their lives. The analysis confirms that higher rates of informal employment (as a fraction of total employment) are associated with higher rates of COVID-19 infection or disease spread. Not surprisingly, countries with relatively larger populations are also more likely to experience higher rates of infection. Given the adverse socioeconomic effects of COVID-19 containment on informal businesses and workers lacking social protection, countries should take proactive steps to curb the spread of infections, treat affected people, and at the same time provide social safety nets and economic relief for informal workers and businesses.